Purchasing fruits at retail store: assessing customer satisfaction / Nurul Afifah Nasir & Nur Suhaida Suboh - Nasir, Nurul Afifah; Suboh, Nur Suhaida (2017)
Customers are the main influential factor of a business success. Therefore, food retailers need to manage and maintain their customer satisfaction. This has been proven crucial by previous studies particularly on how to perceive and retain customer satisfaction. It is believed that fruits purchasing determinants may contribute to customer satisfaction in fruit shop, which should be further examined. The aims of this study are to determine the determinants that may influence the level of customer satisfaction in MBG Fruit Shop such as environment, service employee, fruit freshness, product assortment, and price elements. The participants of this study are customers of MBG Fruit Shop at four selected outlets namely 101 City Mall, NU Central, Tropicana Mall, and Java 33. In finding response of fruit purchasing determinants, self-administered close-ended questionnaires are provided to respondents. From the response, it is found that the key determinants of customer satisfaction are mainly fruit freshness of MBG Fruit Shop and followed by product assortment offered. Additionally, among all attributes in this study, the customers" acceptance level of employee friendliness under the employee service element is slightly lower as compared to other attributes. The results from this study may be useful to fruit businesses owners in deciding whether there is a need for further investment of resources and improving the quality of services, which would increase the level of customer satisfaction.